Induction of Th2 response through TLR2-mediated MyD88-dependent pathway in human microfold cells stimulated with chitosan nanoparticles loaded with Brucella abortus Mdh. (May 2020) - Shim, Soojin; Park, Hyun-Eui; Soh, Sang Hee; Im, Young Bin; Yoo, Han Sang
Abstract: Drug delivery by the nasal or oral route is considered the preferred route of administration because it can induce systemic mucosal immunity. However, few studies have examined the immunogenicity and transport of antigen at the level of the microfold (M) cell, the epithelial cell that specializes in antigen sampling at mucosal surfaces. In our previous study, Brucella abortus malate dehydrogenase (Mdh) was loaded in chitosan nanoparticles (CNs), and it induced high production of proinflammatory cytokines in THP-1 cells and systemic IgA in BALB/C mice. In the present study, an in vitro M cell model was used in which Caco-2 cells and Raji B cells were co-cultured to investigate the impact of the uptake and immunogenicity of B. abortus Mdh on nanoparticle transport in human M cells. Our results showed that loaded CNs induced enhanced transport of Mdh in the M cell model. ELISAs showed significantly higher production of IL-1β and IL-6 in the CN-Mdh stimulation group than that seen in the Mdh stimulation group. The observed increase of gene expression of TLR2, MyD88, TRAF6, IRF4 and CD14 implied that MyD88-dependent TLR2 signaling was activated by stimulation with CNs-Mdh. These results suggest that Mdh and CNs may function synergistically to enhance Th2-related responses triggered by the MyD88-dependent TLR2 signaling pathway and could induce an inflammatory response in M cells as an M cell-targeted delivery system. This study will contribute to the development of not only effective antigens for intracellular bacteria, including B. abortus, but also vaccine delivery systems that target M cells. Highlights: Brucella abortus malate dehydrogenase (Mdh) was loaded with chitosan nanoparticle (CNs) as delivery systems to overcome the barriers associated with the mucosal membrane. In vitro M cell model was developed by co-culture of Caco-2 cells and Raji B cells. B. abortus antigen loaded CNs induced enhanced transport of antigen in the M cell model. The higher production of IL-1β and IL-6 in the CN-Mdh stimulation group were induced than that seen in the Mdh stimulation group. The gene expression of TLR2, MyD88, TRAF6, IRF4 and CD14 implied that MyD88-dependent TLR2 signaling was activated by stimulation with CNs-Mdh.